First and Immediate Responders: Current Capability Needs and Research Challenges. (November 2019) - Prytz, Erik G.; Hallbeck, Susan; Goolsby, Craig; Jonson, Carl-Oscar; Langhelm, Ronald; Mehta, Ranjana K; Peres, S. Camille; Wilson, Darren P.
The purpose of this panel will be to discuss current research and challenges relating to the work of first and immediate responders. The main discussion of the panel will have panelist challenge human factors researchers to consider new directions of research addressing current capability and knowledge gaps faced by the first and immediate responder communities.